An effective strategy to produce highly amenable cellulose and enhance lignin upgrading to aromatic and olefinic hydrocarbons. Issue 1 (31st October 2022) - Vincent Sahayaraj, Daniel; A, Lusi; Kohler, Andrew J.; Bateni, Hamed; Radhakrishnan, Harish; Saraeian, Alireza; Shanks, Brent H.; Bai, Xianglan; Tessonnier, Jean-Philippe
Abstract : Supercritical fractionation of lignocellulosic biomass enhances the production of lignin-derived hydrocarbons and boosts the digestibility of the cellulose-rich pulp. Abstract : Lignin is a promising renewable feedstock for the production of valuable phenolic and hydrocarbon building blocks. However, the economic viability of lignin upgrading strategies has so far been hampered by the recondensation of primary products and the preferential formation of char over bio-oil. Here, we demonstrate that lignin pretreatments effectively lower char formation and enhance carbon volatilization during pyrolysis. Various solvolytic and catalytic pretreatments were investigated using sub- and supercritical ethanol and supported metal catalysts. By combining GPC, GC-FID/MS, elemental analysis, HSQC NMR, and TGA, we decoupled the effects of solvolytic and catalytic steps and identified their independent roles on chemical modifications relative to the parent lignin. The pretreatment step enhanced the production of volatiles and concurrently reduced char formation during fast pyrolysis, from 58 C% to 9 C% for lignin deconstructed at 250 °C using Pd/C. The strategy was then extended directly to lignocellulosic biomass (corn stover, switchgrass, red oak) to fractionate and pretreat lignin in a one-pot approach. The lignin oil obtained from this process exhibited an excellent potential to be converted into platform chemicals. Upon catalytic fast pyrolysis of the lignin oil, 11–14 C% aromatic hydrocarbons were produced, while hydrodeoxygenation yielded 34–40 C% of aromatic hydrocarbons (50–56 C% total hydrocarbons). Similarly, the recovered carbohydrates-rich water-soluble fraction was subjected to hydrodeoxygenation and yielded 10–15 C% of aromatic hydrocarbons and 15–29 C% of C2 –C6 alkenes (32–74 C% total hydrocarbons). Furthermore, the residual pulp recovered from this method was enriched in sugars and was three times more amenable to enzymatic hydrolysis than the parent biomass. This approach provides new opportunities for the selective and effective conversion of lignin into value-added chemicals and, thereby, enhanced carbon recovery, which is vital for implementing biomass as a feedstock for chemical manufacturing.